Topical application of jojoba (Simmondsia chinensis L.) wax enhances the synthesis of pro-collagen III and hyaluronic acid and reduces inflammation in the ex-vivo human skin organ culture model - Tietel, Zipora; Melamed, Sarit; Ogen-Shtern, Navit; Eretz-Kdosha, Noy; Silberstein, Eldad; Ayzenberg, Tomer; Dag, Arnon; Cohen, Guy (Frontiers in Pharmacology, 2024)
Jojoba (Simmondsia chinensis L.) wax was previously reported to increase cutaneous wound healing, ameliorate acne and psoriasis manifestations, and reduce oxidative stress and inflammation. However, its potential cosmetic properties have not been fully investigated. Thus, the current study aimed to evaluate the anti-inflammatory activities of jojoba wax and its impact on the synthesis of extracellular components following topical application. The fatty acid and fatty alcohol profiles of two industrial and two lab-scale cold-press jojoba waxes were analyzed along with total tocopherol and phytosterol content.The dermo-cosmetic effect of all jojoba wax preparations was evaluated ex-vivo, using the human skin organ culture model, which emulates key features of intact tissue. The ability of jojoba wax to reduce secreted levels of key pro-inflammatory cytokines and the safety of the applications in the ex-vivo model were evaluated. In addition, the impact on the synthesis of pro-collagen and hyaluronic acid levels upon treatment was investigated. The results demonstrate that topically applied jojoba wax can reduce LPS-induced secretion of IL-6, IL-8, and TNFα by approx. 30% compared to untreated skin. This effect was enhanced when treatment was combined with low non-toxic levels of Triton X-100, and its efficacy was similar to the anti-inflammatory activity of dexamethasone used as a positive control. In addition, mRNA and protein levels of collagen III and synthesis of hyaluronic acid were markedly increased upon topical application of jojoba. Moreover, the enhanced content of extracellular matrix (ECM) components correlated with the enhanced expression of TGFβ1. Collectively, our results further demonstrate that jojoba can reduce local skin inflammation, and this effect may be increased by emulsifier which increases its bioavailability. In addition, the finding that topical application of jojoba wax enhances the synthesis of pro-collagen and hyaluronic acid and may be beneficial in the treatment of age-related manifestations.